Deconstructing Socio-Psychological Prejudices: A Study of Mahesh Dattani‟s“Bravely Fought The Queen” - BATRA, JAGDISH (International Journal of Psychosocial Rehabilitation, 2020)
Mahesh Dattani is a leading Indian playwright who writes in English. He is the first such writer who has been bestowed the national SahityaAkademi Award for his contribution to the field of English drama. What distinguishes him from run-of-the-mill dramatists is his reformatory zeal, something that puts him in league with the likes of G.B. Shaw. His themes are invariably linked to present-day problems of socio-cultural importance. Thus, Dattani’s plays touch upon gay and lesbian relations, status of the marginalized sections like neutars, women, children and physically challenged people. Besides, he has written on victims of AIDS and communal riots. In the play “Bravely Fought the Queen,” we come across his sharp disapproval of social hypocrisy as reflected in various rules governing women, family and social life. He rips the veneer off the face of people leading inauthentic lives in matters of sexual preference and loyalty towards life partner. In addition to it, Dattani also underlines the immoral lure of the lucre which is prioritized over all moral values even as people feign otherwise. My paper aims to bring out this characteristic of Dattani’s approach taking into account the impact as made out from critiques.